Pengaruh Partisipasi Anggaran, Kepercayaan dan Komitmen Organisasi Terhadap Kinerja Karyawan Rumah Sakit Swasta Type C Di Provinsi Lampung - Nani Kustina (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2021)
The health department is an inseparable part, and the community urgently needs this department, one of which is the hospital. Today, the number of public and private hospitals makes competition in the health sector more intense. Therefore, the hospital must always improve management performance to achieve its goals. One of the efforts to improve hospital management performance is to try to maintain the recognition of these public/private hospitals. Data collection is used in the form of master data and auxiliary data. Use statistical data analysis to test the data, which is processed using computer software (ie Smart PLS). The samples for this study are 70 employees from Pertamina Bintang Amin Hospital and Islam Asy Syifaa BandarJaya Hospital. Based on quantitative analysis, it is found that budget participation has a positive impact on employee performance. The t-score is 2.085, and trust has a positive effect on employee performance. The t-statistic value is 2.245, and organizational commitment has a positive impact on employee performance. The t value of the statistics is 2.114. The R2 value of performance composition is 0.373, which means that budget participation, trust and organizational commitment can explain 0.373 or 37.3% of the variability of performance composition, while the rest (100%-37.3 = 62.7%) is explained by other unchecked factors . According to the research results and hypothesis testing, the following conclusions can be drawn: budget participation has a significant positive impact on employee performance, trust has a significant positive impact on employee performance, and organizational commitment has a significant positive impact on employee performance.